A checklist of Nylanderia (Hymenoptera: Formicidae: Formicinae) from Hong Kong and Macao SARs, with an illustrated identification key for species in Southeast China and Taiwan - Silva, Thiago S R; Hamer, Matthew T; Guénard, Benoit (Zootaxa, 2023)
Species of the ant genus Nylanderia constitute some of the most common ground dwelling Formicinae in tropical and subtropical areas. The genus includes numerous species introduced into new regions, especially within urban or disturbed environments. Here, we review the Nylanderia species found within Hong Kong and Macao, which are both highly urbanized regions and of critical importance to Southern China’s policy-makers and non-governmental actors concerned with the regional spread of non-native species. A total of 11 species and 2 morphospecies are recorded in Hong Kong and 6 species and 2 morphospecies are recorded in Macao. We also provide a list of new records for the genus in Hong Kong and Macao, along with taxonomic accounts for all the species recorded. Additionally, the present work provides an illustrated identification key for the species of Nylanderia occurring in Southeast Mainland China and Taiwan. We briefly discuss the possible biogeographical implications of our findings, providing additional support to the exotic status of N. bourbonica in continental Southeast Asia. Lastly, we give our perspective on the ramifications of local inaccessibility to type specimens to current taxonomic practices.